2015
DOI: 10.1371/journal.pone.0129276
|View full text |Cite
|
Sign up to set email alerts
|

Oral Delivery of a Novel Attenuated Salmonella Vaccine Expressing Influenza A Virus Proteins Protects Mice against H5N1 and H1N1 Viral Infection

Abstract: Attenuated strains of invasive enteric bacteria, such as Salmonella, represent promising gene delivery agents for nucleic acid-based vaccines as they can be administrated orally. In this study, we constructed a novel attenuated strain of Salmonella for the delivery and expression of the hemagglutinin (HA) and neuraminidase (NA) of a highly pathogenic H5N1 influenza virus. We showed that the constructed Salmonella strain exhibited efficient gene transfer activity for HA and NA expression and little cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…These findings clearly indicate that Salmonella -based influenza vaccines can stimulate efficient Th1 type of immunity and can protect the hosts from pathogenic influenza infections. Our results are in agreement to the previously published reports [ 18 , 32 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings clearly indicate that Salmonella -based influenza vaccines can stimulate efficient Th1 type of immunity and can protect the hosts from pathogenic influenza infections. Our results are in agreement to the previously published reports [ 18 , 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the Salmonella -based HA, NA and M2e vaccines not only generated efficient humoral responses but also stimulated high level of antigen-specific cellular responses. Previous study have shown that immunization with Salmonella -based HA and NA vaccination elicits efficient cellular immune responses and protects the mice against the homologous and heterologous H5N1 and H1N1 challenges, respectively [ 32 ]. Our results show that vaccinated PBMCs stimulated with recall inactivated H7N9 antigen resulted in higher proliferative responses compared to the control chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Exploiting live attenuated Salmonella system to deliver IBV S1 immunogenic protein is a highly economical vaccination strategy that allows for a quick response to deployment of vaccines, as it circumvents the need for a constant supply of specific-pathogen-free (SPF) embryonated eggs. Furthermore, Salmonella -based vaccination strategy induces efficient antigen-specific humoral and cell-mediated immunity [ 17 19 ], and these vaccines have already been approved for use in poultry [ 20 ]. Herein, we show that attenuated SG mutant delivering immunogenic S1 protein elicited efficient IBV-specific humoral and cell-mediated immune (CMI) responses and conferred significant protection against a virulent IBV challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, influenza vaccines need to be annually updated pertaining to the antigenic changes of circulating field strains. Live bacterial vectors are a promising approach to deliver immunogenic proteins of AIV to the immune system [21]. Studies have demonstrated that attenuated Salmonella based system carrying various heterologous viral antigens elicit efficient systemic and mucosal immune responses [22].…”
Section: Introductionmentioning
confidence: 99%